Dynamic modelling of a spar buoy wind turbine - Tomasicchio G. R.; Avossa A. M.; Riefolo L.; Ricciardelli F.; Musci E.; D’Alessandro F.; Vicinanza D. (Volume 10: Ocean Renewable Energy, 2017)
In the present paper, the dynamic response of a spar buoy wind turbine under different wind and wave conditions is discussed. Physical model tests were performed at the Danish Hydraulic Institute (DHI) off-shore wave basin within the EUHydralab IV Integrated Infrastructure Initiative. The OC3-Hywind spar buoy was taken as reference prototype. A spar buoy model, 1:40 Froude-scaled, was tested using long crested regular and irregular waves, orthogonal (0 degrees) and oblique (20 degrees) to the structure. Here the results concerning regular waves, with incidence orthogonal to the structure, are presented; the selected tests considered rotating and non-rotating blades. Measurements of displacements, rotations, accelerations, forces response of the floating structure and at the mooring lines were carried out. Based on the observed data, FAST wind turbine simulation tool, developed and maintained by the U.S. Department of Energy's (DOE's), National Renewable Energy Laboratory (NREL), was calibrated and verified. The numerical model takes into account the wave induced response and the effects of the mooring lines on the overall system. The adopted spar buoy has three equally spaced mooring lines that were modelled as quasi-static taut or catenary lines through MAP++ (static module) and MoorDyn (dynamic module) in the FAST simulation tool. The tensions along the fairleads of the three mooring lines were examined. At the end of the calibration procedure, the numerical model was successfully used to simulate the dynamic motions of the floating wind turbine under combinations of wind and sea states for the selected wave attacks. All data from the DHI tests were converted to full scale using Froude scaling before being analyzed.